Chronic Stress in Battery Hens: Measuring Corticosterone in Laying Hen Eggs - Bulmer, Elena; Gil, Diego (International Journal of Poultry Science, 2008)
There has been growing social and scientific interest in recent years in laying hen welfare. Stress is an animal welfare parameter that has been found to alter laying hens` physiology and social behaviour. Our study aims to test the effects of the different housing systems (laying cage, barn and free range) on the laying hens` welfare. In this study we have taken a new approach to determine stress levels by measuring corticosterone and androgen concentrations in the eggs laid by hens housed in different farming systems. We found no relationship between commercial egg production type and androgen (testosterone and androstenedione) levels. Contrary to our expectations, we observed an almost significant positive trend between corticosterone levels and welfare quality: free range eggs contained the highest corticosterone concentrations. This would initially suggest that free range hens are more stressed than battery or barn hens. However, considering that chronic stressors can reduce an organism`s hormonal output, our results could suggest that the low levels of corticosterone in battery hens are an indication of a chronic stress situation. Our data suggest that measuring corticosterone in eggs is a novel non-invasive method to determine stress levels in laying hens. This study would however need to be combined with a number of parameters (health, production and behaviour) to get an encompassing measure of laying hen welfare.